THE COMPARATIVE STUDY OF RAILWAY BRIDGE DESIGN LOAD BETWEEN PM 60/2012 AND EN 1991: 2-2003 - Barasa, Willy; Fiantika, Thiya; Purnomo, Dwi Agus; Aspar, Wimpie Agoeng Noegroho (Deputi TIRBR-BPPT, 2020)
In Referring to the government programs on the increasing speed of the Jakarta-Surabaya express train in 2017, problems arise in the field, namely the potential increase in freight transportation via the railway line where an increase in loading is required on the railway especially for the existing bridge. This Research was implemented by increasing of the loading of the standard PM 60/2012 bridge to be compared with the EN1991: 2/2003 standard. This research analyzed the increase in structural strength of the 30m span steel bridge of the BH 182 constructed in Operational Region 2 Bandung as a results of loading adjustment from PM 60/2012 to EN 1991:2/2003.This paper explained an effect caused by increasing load on railway bridges with similar span and materials on normal plane, shear plane, moment and deflection. Structural analysis and calculation was performed by means of SAP2000 software. Results of analysis showed that standard equalization of EN 1991:2/2003 caused increasing percentage of loading combination of Comb L, normal plane, shear plane, moment plane, and deflection are of 35%, 60%, 71%, and 31%, respectively. While for Comb R loading combination for normal plane, shear plane, moment plane, and deflection are of 30%, 64%, 71%, and 30%, respectively.Keywords : PM 60 of 2012; EN1991:2-2003; SAP2000; Normal Field; Shear Field; Moment Field; Deflection.